Prevention of adhesion bands by ibuprofen‐loaded PLGA nanofibers. (3rd August 2016) - Jamshidi‐Adegani, Fatemeh; Seyedjafari, Ehsan; Gheibi, Nematollah; Soleimani, Masoud; Sahmani, Mehdi
Abstract : In this study, prevention of the adhesion bands and inflammatory features has been investigated using poly (lactic‐ co ‐glycolic acid)‐ibuprofen (PLGA‐IB) nanofibrous meshes in a mice model. To find the optimized membrane for prevention of postoperative adhesion bands, we have compared PLGA‐IB group with PLGA, IB, and control groups in a mice adhesion model. Two scoring adhesion systems were used to represent the outcome. According to the results obtained in this study, the PLGA‐IB nanofiber membrane showed a greater reduction in adhesion band than other groups. In conclusion, among FDA‐approved polymers and drugs, PLGA‐IB meshes could be applicable as a potential candidate for prevention of postoperative abdominal inflammation and adhesion bands formation. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:990–997, 2016